The comparative evaluation of plant adaptogenes’ hepatoprotective properties on the experimental model of rat liver chronic alcohol dama ge in vivo - Hubich, Aksana I.; Dashkova, Yana Yu.; Krivlenya, Ina N. (Experimental Biology and Biotechnology, 2019)
This work is devoted to the study of the effectiveness of biochemical liver damage markers and lipid peroxidation correction by plant adaptogens (Sideritis scardica, Hibiscus sabdariffa, Rhododendron adamsii Rehder) in laboratory rats with experimental chronic alcohol intoxication. It was shown that the using of all drugs studied contributes to the normalization of liver damage indicators (alkaline phosphatase and alanine aminotransferase activity, the content of free and bound bilirubin in the blood serum) and lipid peroxidation markers (the content of reduced SH-groups and TBA-active products, catalase and superoxide dismutase activity in the liver homogenate). It was demonstrated that the most pronounced antioxidant and hepatoprotective effects in this model, comparable to the action of classical hepatoprotectors «Hepsil-Rn» and «Essentiale Forte», had decoctions of Sideritis scardica and Rhododendron adamsii Rehder which may be due to the high content of flavonoids and unsaturated fatty acids in their composition.